Development of a Flip Book-Based Practical Guide for Chocolate Cake Decorations - Mentari Arisyid Mulyadi; Titis Budi Rahayu; Nirmalasari Nirmalasari (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to develop a practicum guide on chocolate cake decoration for the Cake Decoration course using the Plomp development model, which consists of three stages: preliminary analysis, design, and assessment. A needs analysis was conducted through questionnaires distributed to lecturers and students of the Culinary Education Study Program at Universitas Negeri Medan. The results showed that 93.83% of lecturers and 83.74% of students required a practicum guide in flipbook format as a learning medium. In the design phase, the guide was developed using applications such as Heyzine Flipbook and Canva, incorporating interactive multimedia elements. The guide was validated by subject matter experts and media experts, yielding an average score of 94.75 for content and 87.69 for media, both categorized as highly feasible. Practicality testing by students resulted in an average score of 87.88, indicating a high level of practicality. These findings demonstrate that the developed flipbook-based practicum guide is both appropriate and effective for use in the Cake Decoration course.